Effect of pre-sowing treatment on seed germination of Ixora coccinea L. - Shinde, Amruta Shivajirao; Chavan, Niranjana Sunil (Current Botany, 2017)
Ixora coccinea L. is ornamentally and medicinally important coastal plant also associated with mangroves of Sindhudurg and Ratnagiri district. In present study seeds of I. coccinea were treated with cold water, 50°C hot water, germinator solution and also 100 ppm, 200 ppm, 500 ppm GA. Germination percentage were measured every day until no germination were observed. Data was analysed using analysis of variance (ANOVA) and significant mean difference in pair of treatments was analysed by using t-Test. Seeds of I. coccinea treated with 100 ppm GA showed highest germination percentage i.e. 90% followed by hot water treated seeds and it showed 85% germination. Seeds were treated with GA, Hot water, Germinator, soaking in cold water showed significant difference in between treatments ( p<0.05). Overall results suggest that 100 ppm GA and hot water treatment used for enhance the germination of I. coccinea seeds.